2020
DOI: 10.3390/ijerph17186820
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Occupational Exposure Assessment of Aerosols

Abstract: Exposure science is underpinned by characterization (measurement) of exposures. In this article, six recent advances in exposure characterization by sampling and analysis are reviewed as tools in the occupational exposure assessment of aerosols. Three advances discussed in detail are (1) recognition and inclusion of sampler wall deposits; (2) development of a new sampling and analytical procedure for respirable crystalline silica that allows non-destructive field analysis at the end of the sampling period; and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 79 publications
(102 reference statements)
0
3
0
Order By: Relevance
“…Particle size distribution information is also added ( Table 7 ), noting that, depending on size distribution and concentration, the deviation in the particle concentration number measured by the different instruments can be up to 50% [ 30 ]. For NO dust collection sampling, cassette wall losses should be reported; in conductive cassettes, the wall losses for respirable dust have been reported to be up to 56% as median wall deposits [ 37 ]. Size distribution reporting can be shortened with values of a fitted log-normal distribution that further simplifies the data reporting and applicability.…”
Section: Resultsmentioning
confidence: 99%
“…Particle size distribution information is also added ( Table 7 ), noting that, depending on size distribution and concentration, the deviation in the particle concentration number measured by the different instruments can be up to 50% [ 30 ]. For NO dust collection sampling, cassette wall losses should be reported; in conductive cassettes, the wall losses for respirable dust have been reported to be up to 56% as median wall deposits [ 37 ]. Size distribution reporting can be shortened with values of a fitted log-normal distribution that further simplifies the data reporting and applicability.…”
Section: Resultsmentioning
confidence: 99%
“…The Li mass fractions of these tourmalines vary over three orders of magnitude. Homogeneity tests by SIMS demonstrated that the 7 Li/ 6 Li and 18 O/ 16 O isotope ratios were constant within AE2.2 and AE0.2& (1SD), respectively, at sub-ng test portion masses. Reference values reported for d 18 O, D 17 O and d 7 Li in these tourmaline RMs were based on results for bulk mineral analyses undertaken at several independent laboratories.…”
Section: Reference Materials and Data Qualitymentioning
confidence: 95%
“…(2015) . The Wall losses of SC.1.106 and GK2.69 sampler is not reported but for other respirable samplers’ using conductive cassettes the median wall losses is shown to vary from 5% to 56% with a maximum loss varying from 12% to 93% ( Harper, 2020 ). In Koivisto et al .…”
Section: Methodsmentioning
confidence: 99%